The Effects of Pasteurization and Beer Type on the Functional Compounds and Flavor Substances in Beer - Jiahui Ding; Xiaoping Hou; Jianghua Li; Xinrui Zhao; Shumin Hu (Beverages, 2025)
The study of functional compounds is of great importance for the production of nutrient-rich and flavorful beer. In this study, the effects of the pasteurization process and beer type (lager and ale, draft beer, and ripe beer) on the types and contents of functional compounds were investigated, including the derivatives of amino acids (γ-aminobutyric acid and glutathione), β-glucan, phenolic acids, vitamin B, and volatile compounds. Among the six different types of beers tested, it was found that the concentration of functional compounds in ale was higher than that in lager. In addition, the process of pasteurization resulted in the loss of B vitamins and ferulic acid and an increase in some off-flavors such as aldehydes. The results of this study can aid in the development of novel functional beer and new strategies to improve beer quality.